Jet fuel hedging strategies in the airline industry - Mitrega, Michal; Málek, Jiří, 1953-; Baran, Jaroslav; Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví (2012)
This thesis aims to provide corporate treasuries of international airlines with practical jet fuel hedging strategies that would raise companies' market value and lower their cost of equity. The current work available on the subject focuses mostly on the theory of hedging. The case study that constitutes the second half of this work clearly explains both the errors and achievements of most of the major airlines between 2006 and 2012 while the first half provides a theoretical framework for hedging with practical conclusions that can be used in formulating and enforcing hedging policies.
Vedoucí práce: Jiří Málek
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví, 2013
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2013
Způsob přístupu: Internet
Keywords: finance [obor dipl. práce]; diplomové práce; master's theses